Synthesis of Highly Thermostable and Transparent Colorless Polyimides Based on a Semi‐aromatic Tetracarboxylic Anhydride. Issue 9 (28th February 2023) - Zhou, Di; Peng, Qing; Kong, Ling‐lu; Liu, Shu‐mei; Yuan, Yan‐chao; Ma, Yu‐guang; Mo, Yue‐qi; Qin, Dong‐huan; Zhao, Jian‐qing
Abstract: A semi‐aromatic tetracarboxylic dianhydide, 1, 2, 3, 4, 5, 6, 7, 8‐octahydroanthracene‐2, 3, 6, 7‐tetracarboxylic dianhydride (OHADA), was successfully synthesized via a Diels Alder reaction. Two polyimides (OHADA‐TFDB and OHADA‐BAFL) were obtained via one‐step polycondensation of OHADA with 2, 2′‐Bis(trifluoromethyl)benzidine (TFDB) and 9, 9‐bis(4‐aminophenyl)fluorene (BAFL) in m‐cresol, respectively. OHADA‐TFDB has better solubility and processibilty than OHADA‐BAFL, but colorless OHADA‐BAFL exhibits higher thermal stability and lighter color. OHADA‐TFDB and OHADA‐BAFL display high glass transition temperatures (Tg s) of 339 °C/385 °C from DSC curves and 335 °C/395 °C from TMA trances, respectively. Their decomposition temperatures at 5 % weight loss (Td5 ) are above 537 °C/546 °C under nitrogen. These results are much better than those from wholly alicyclic tetracarboxylic dianhydride‐based polyimides (PIs), which can be attributed to the benzene moiety in OHADA. Furthermore, OHADA‐TFDB and OHADA‐BAFL exhibit good optical transparency with the cutoff wavelength of 315 nm/305 nm, light transmittance over 74 %/72 % at 400 nm and 84 %/80 % at 500 nm, which indicates it is an effectively way to suppress the formation of charge transfer complex (CTC) by introducing alicyclic moieties in OHADA. Their mechanical properties are also characterized in this study. Abstract : Two transparent polyimides (OHADA‐TFDB and OHADA‐BAFL) from a semi‐aromatic dianhydride OHADA were synthesized via one‐step poly‐condensation. OHADA‐TFDB has better solubility and processibilty than OHADA‐BAFL, but colorless OHADA‐BAFL exhibits higher thermal stability and lower YI. Their high T5 s and T g s are among the highest rank in the colorless PIs and superior to those from wholly alicyclic tetracarboxylic dianhydride‐based PIs.